Inelastic seismic response of fixed and pile supported structures by considering different member hysteretic models. - Perpustakaan UGM, i-lib ([Yogyakarta] : Fac. of Geography Gadjah Mada Univ., 2001)
Simplification on the structural analysis is often done to avoid the complexity of the problems. The structural analysis is straight forward if the building is assumed to be fixed at their column bases (Fix structure). This analysis ignores the effect of the soil on the structural response. In this analysis, all imparted seismic energy is accommodated by the structure and transferred in term of kinetic, strain, viscous and hysteretic energy. However, soil is not an infinitely rigid material, as it has flexibility. When the soil-flexible pile interaction is considered, its interaction may able to modify the vertical seismic propagation and impose vertical, horizontal and rotation vibration modes. In this analysis, part of the seismic imparted energy will be reflected back to the soil media in term of radiation damping (Flex structure). The structural analysis becomes more realistic when the soil-pile interaction is considered. Research on the effect of pile foundation interaction on the inelastic Flex building and response of Fix inelastic building has been conducted, and the result is presented in this paper. In this research, the structural model was 12-storey fully ductile frame building, located at Indonesian earthquake region-3 and designed according to the SK-SNI 1991 Codes. The building model was excited by the 1940 El Centro North-South component. Four member hysteretic models i.e Bilinear, Clough, Takeda and Q-Hyst models have been considered. The inelastic seismic response of Fix and Flex structure then be compared. The Flex structure exhibits higher in the most inelastic structural response than the Fix one. The fatter hysteretic model (such as the Bilinear model) implies that the structure becomes more stiff and causes smaller in most structural response. The capability of the member hysteretic model to dissipate energy is not always affected by its fatness but more dependent on the unloading, reloading stiffness and amplitude of motions. Since its relationship is relatively strong, the inter storey drift and beam curvature ductility demand can be used to predict the member damage index.